Internet technology companies as evidence intermediaries - Yan Fang (Virginia law review, 2024)
Search warrants, subpoenas, and other forms of compulsory legal process are essential for legal parties to gather evidence. Internet technology companies increasingly control wide-ranging forms of evidence, yet little is known about how these companies fulfill their compulsory legal obligations. This Article presents an original study of internet technology companies as evidence intermediaries: third-party organizations that control access to evidence routinely sought by legal parties. Drawing on in-depth qualitative interviews with companies' legal and compliance staff and with law enforcement agents, I show how company processes for responding to search warrants cannot be neatly categorized within the existing literature's dichotomy of cooperation or resistance. Rather, the responses consist of makeshift measures that companies have developed to manage predicaments arising from the imprecise or impracticable wording of warrants. These measures can affect the evidence that is ultimately available for use in legal proceedings. They can also untether the scope of searches-as they are carried out-from the procedures of the Fourth Amendment. This Article contends that, because judicial officers are likely ill-equipped to oversee problematic company practices, a variety of institutional interventions to supplement existing court oversight of search procedure should be considered.